FINANCIAL FINANCING AND ITS IMPACT ON SUPPORTING SMALL AND MEDIUM ENTERPRISES IN THE ISLAMIC ECONOMY - Dr. Mostafa Kazemi Najafabadi , M. Shafiq Muhammad Mankhi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Financial financing is one of the branches of economic theory, and it stems from the desire of individuals and business establishments to achieve the maximum possible level of luxury. This research aims to analyze the various financing methods from the perspective of the Islamic economy, and their impact on supporting small and medium enterprises based on credit with interest, and replaces them with Islamic financing forms Convenience. To achieve this, the researcher used the descriptive analytical approach to describe and analyze available data. The research reached several results, including: Islamic banks that deal with public funds must direct a direction by working in financing small and medium projects that will gain them advantages that make them capable with competition and development. The researcher concluded several recommendations, the most important of which is the establishment of specialized Islamic investment funds to finance small and medium projects emanating from Islamic banks, in addition to reducing the rates of profitability of banks in terms of social responsibility, and benefiting from the experiences of developed countries, especially the experiences of developing countries (the Iran experience) .